Immigration in Latin America in Democracies with Alzheimer's - Abedrapo, Jaime (2023)
Liberal democracies in postmodern times face challenges such as climate change, access to clean and renewable energy sources, and immigration. In this regard, we will observe the trends to address these issues, with a special focus on Latin America and immigration. In this regard, the civilizational crisis we are witnessing tends to forget its cultural origins, therefore, its legitimacy based on the norms that founded the post-World War II world order. An issue that we have understood as an affectation of Alzheimer’s, which precisely prevents immigration phenomena from being understood from their causes.